O descortinar das manifestações da cultura organizacional: a percepção dos técnicos-administrativos e gestores da Reitoria da UFT - Parente, Míriam Lucas da Silva (Universidade Federal do Tocantins, 2016)
In the present study we sought to understand how the individual-organization relationship, involving values, behavioral and symbolic aspects may influence the organizational culture at the Federal University of Tocantins, UFT. The analysis has the intention to capture aspects of the complexity and dynamics of the organization, by clipping of the organizational culture. For this, three specific objectives were established: identify the perception of understanding of administrative managers and technicians on organizational culture; know the critical points of this culture; and verify the contribution of management practices in the printing sense of belonging. The “culture of UFT” in this context is understood as a set of ideas, values, worldviews and knowledge built and shared ephemerally by individuals in an organization. The case study is based on an approach both quantitative and qualitative and data were collected through the following methodological strategies: bibliographical and documentary research, questionnaires to technical and administrative staff and carrying out semi-structured interviews with managers, both established at the Rectory of UFT, located in the Palmas Campus. For data analysis, it was used descriptive statistics, content analysis and triangulation of data. The results show that both the technical-administrative and managers are aware of the importance of organizational culture in professional and institutional human development. However, these perceptions differ in several respects. According to the authors surveyed, some critical points (issues related to meritocracy, assessment, planning, communication, appreciation, career, bureaucracy, etc.) negatively impact on organizational culture, limiting the individual-organization relationship. Moreover, it was found that the institution does not have a policy specifically driven organizational culture, able to support practices that minimize conflicts of interest that permeate the organization. When it was examined, existing actions do not correspond to the needs and desires of the public searched. Therefore it can be inferred that the UFT, through its managers, must rethink and improve their management practices by providing subsidies that provide a balanced and sustainable work environment and a positive influence on organizational commitment.